Fungal Infections: An Overview (Homoeopathy for All, 2024)
Fungal infections are caused by  various species of fungi that can  invade and infect various parts of the  human body, from superficial layers  like skin and mucous membranes  to deeper tissues and organs.  While some fungal infections  remain mild and can resolve with  minimal intervention, certain  infections become severe and  even life-threatening, especially in  individuals with weakened immune  systems. Fungi that lead to human  infections often act as opportunistic  pathogens, taking advantage of the  host’s compromised immunity to  cause disease. These infections can  range from common conditions like  athlete’s foot and ringworm to more  serious infections like Aspergillosis  and Candidiasis, especially in those  with underlying health issues.
Keywords: Globally; COVID-19; Mucormycosis